Synthesis and Characterization of Chloridobis(dimethylglyoximato)4-(2-ferrocenylvinyl)pyridinecobalt(III): A New Heterobinuclear Cobaloxime - Sebastián Pizarro; Guillermo Saá; Francisco Gajardo; Alvaro Delgadillo (Journal of Chemistry)
The synthesis of a new heterobinuclear cobaloxime with 4-(2-ferrocenylvinyl)pyridine, fcvpy, is reported. The complex [CoCl(dmgH)2(fcvpy)], where dmgH2 is dimethylglyoxime and dmgH is dimethylglyoximato, has been characterized by 1H-NMR, UV-Vis, cyclic voltammetry, and elemental analysis. The cyclic voltammogram of this complex shows a fc/fc+ reversible wave at +0.58 V versus Ag/AgCl, one irreversible wave, Epc = −0.54 V versus Ag/AgCl, assigned to the reduction of Co(III) to Co(II), and two quasireversible processes at −1.02 V and −1.10 V versus Ag/AgCl associated with the reduction of Co(II). The complex showed ferrocene-ligand charge transfer bands at 334 nm and 505 nm. TDDFT/B3LYP/6-31G(d) calculations support this assignation.